Mesenchymal stem cells and exosomes in ischemic brain injury: a review - Xu, Haiyan; Yang, Lanlan; Wang, Weitie; Zhang, Chengwei (Frontiers in Genetics, 2025)
Stroke poses a serious threat to human health and life, serving as a leading cause of death and disability in adults. The incidence rate of stroke continues to rise annually. Following the onset of ischemic stroke, most patients experience a period of spontaneous recovery. Neural repair after cerebral ischemia is closely associated with neurovascular plasticity, which facilitates the regeneration and repair of nerves and blood vessels in the ischemic injury area. Mesenchymal stem cells (MSCs), adult stem cells isolated from bone marrow or other tissues, can differentiate into various cell types and possess characteristics such as self-renewal, low immunogenicity, and easy of isolation. Exosomes are regarded as the primary mediators of MSC functions. These specialized extracellular vesicles play critical roles in intercellular communication, targeted transport, and regulation of recipient cell functions through their surface molecules and cargo (e.g., proteins, RNA, and other bioactive factors). Studies demonstrate that MSCs and their exosomes participate in both neuronal and vascular endothelial cell damage and repair after stroke. They exert distinct effects at different stages of cerebral ischemia injury, promoting angiogenesis, neurogenesis, and reducing inflammation. While preclinical studies show promising therapeutic potential, clinical translation faces challenges such as standardization of exosome isolation, optimal dosing, delivery methods, and long-term safety evaluation. Future research should focus on overcoming these barriers to facilitate their application in stroke therapy. This review summarizes current research on the therapeutic potential of MSCs and their exosomes in ischemic brain injury.